Integrating E-cadherin expression levels with TNM staging for enhanced prognostic prediction in colorectal cancer patients - Jae-Ghi Lee; Ilkyu Park; Hannah Lee; Seungyoon Nam; Jisup Kim; Won-Suk Lee; Myunghee Kang; Jung Ho Kim (BMC Cancer)
Abstract Purpose This study aimed to investigate the clinical significance of E-cadherin expression levels in colorectal cancer tissues and explore the relationship between E-cadherin expression and tumor node metastasis (TNM) stage. The goal was to establish a more accurate prognostic prediction for colorectal cancer patients by analyzing E-cadherin expression levels alongside TNM staging. Methods The study examined colorectal cancer patients by dividing them into groups based on E-cadherin expression levels. It then assessed their 5-year event-free survival (EFS) and disease-specific survival (DSS) hazard ratios (HRs). Additionally, the prognosis of patients was analyzed by combining E-cadherin expression levels with TNM staging, particularly focusing on patients in stages III and IV. Results The E-cadherinLow group had significantly worse outcomes, with HRs of 2.30 for EFS and 2.76 for DSS compared to the E-cadherinHigh group. When combined with TNM stage III/IV, patients with E-cadherinLow expression showed a poor prognosis, with HRs of 1.93 for EFS and 2.35 for DSS compared to those with E-cadherinHigh expression at the same TNM stage. Conclusions Low levels of E-cadherin expression are associated with a poor prognosis and decreased survival in colorectal cancer patients. Combining E-cadherin expression levels with TNM staging provides a more precise prediction of patient prognosis and survival, potentially guiding personalized treatment strategies.